Prehospital stroke mimics in the Stockholm Stroke Triage System - Sjöö, Mimmi; Berglund, Annika; Sjöstrand, Christina; Eriksson, Einar E.; Mazya, Michael V. (Frontiers in Neurology, 2022)
Abstract Introduction: In 2017, Stockholm implemented a new prehospital Stroke Triage System (SSTS), directing patients with a likely indication for thrombectomy to the regional comprehensive stroke center (CSC), based on symptom severity and teleconsultation with a physician. In Stockholm, 44% of prehospital code-stroke patients are stroke mimics. Inadvertent triage of stroke mimics to the CSC could lead to inappropriate resource utilization. Aims: Compare characteristics between 1) triage positive stroke mimics and stroke (TP-Mimics and TP-Stroke) and 2) triage negative stroke mimics and stroke (TN-Mimics and TN-Stroke), and 3) compare the distribution of stroke mimic diagnoses between triage positive and negative cases. Methods: This prospective observational study collected data during between October 2017 to October 2018, including 2905 patients with suspected stroke, transported by code-stroke ambulance to a Stockholm Region hospital. Patients directed to the CSC were defined as triage positive. Those directed to the nearest stroke center were defined as triage negative. Results: Compared to individuals with TP-Stroke (n=268), those with TP-Mimics (n=55) were younger, median 64 vs. 75 years; P<0.001 and had lower NIHSS score, median 7 vs. 15, P <0.001. Similarly, TN-Mimics (n=1221) were younger than TN-Stroke (n=1361), median 73 vs 78 years; P<0.001 and had lower NIHSS scores, median 2 vs. 4, P<0.001.” Functional paresis was more common in TP-Mimics than in TN-Mimics, 18/55 (32.7%) vs. 82/1221 (6.7%); P<0.001. Systemic infection was less common in TP-Mimics than in TN-Mimics, 1/55 (1.8%) vs 160/1221 (13.1%); P<0.011. There was a trend towards “syncope, hypotension, or other cardiovascular diagnosis” being less common in TP-Mimics than in TN-Mimics, 1/55 (1.8%) vs 118/1221 (9.7%); P<0.055. Conclusions: In the SSTS, triage positive and negative stroke mimics were younger with less severe symptoms than stroke patients. All TP-Mimics had a hemiparesis, yet overall, less severe symptoms versus true stroke, albeit more severe than TN-Mimics triaged to nearest hospital. Over-triage of functional paresis to the CSC was relatively common. Meanwhile, a large majority of cases with minor symptoms caused by stroke mimics was triaged correctly by the SSTS to the nearest stroke center.